2011
DOI: 10.1007/s00467-010-1740-6
|View full text |Cite
|
Sign up to set email alerts
|

Is cellular senescence important in pediatric kidney disease?

Abstract: Somatic cellular senescence (SCS) describes the limited ability of cells to divide. Normally, SCS is associated with physiological aging, but evidence suggests that it may play a role in disease progression, even in young patients. Stressors such as acute injury or chronic inflammation may induce SCS, which in turn exhausts organ regenerative potential. This review summarizes what is known about SCS in the kidney with aging and disease. As most patients with chronic kidney disease (CKD) also develop cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…While studies have shown that oxidative DNA damage and the senescence markers p16 and p21 are elevated in atherosclerotic plaque and adult vessels from CKD patients, 11,29,30 this is the first study to show increased levels of these markers in vessels from young children, who are free of confounding factors including atherosclerosis, providing compelling evidence that the vascular pathology observed in these patients is closely associated with premature aging. 31,32 Our data suggest that oxidative DNA damage accrual begins in predialysis CKD5, as levels of 8-oxo-dG and p21 were significantly elevated at this stage, but is accelerated in the dialysis milieu leading to unrepaired DNA damage and stress-induced premature senescence a hallmark of which is p16 accumulation. 29,31…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While studies have shown that oxidative DNA damage and the senescence markers p16 and p21 are elevated in atherosclerotic plaque and adult vessels from CKD patients, 11,29,30 this is the first study to show increased levels of these markers in vessels from young children, who are free of confounding factors including atherosclerosis, providing compelling evidence that the vascular pathology observed in these patients is closely associated with premature aging. 31,32 Our data suggest that oxidative DNA damage accrual begins in predialysis CKD5, as levels of 8-oxo-dG and p21 were significantly elevated at this stage, but is accelerated in the dialysis milieu leading to unrepaired DNA damage and stress-induced premature senescence a hallmark of which is p16 accumulation. 29,31…”
Section: Discussionmentioning
confidence: 72%
“…31,32 Our data suggest that oxidative DNA damage accrual begins in predialysis CKD5, as levels of 8-oxo-dG and p21 were significantly elevated at this stage, but is accelerated in the dialysis milieu leading to unrepaired DNA damage and stress-induced premature senescence a hallmark of which is p16 accumulation. 29,31…”
Section: Discussionmentioning
confidence: 72%
“…oxidative stress) may cause accelerated telomere attrition (28) or directly damage DNA, leading to the induction of the DNA damage response via ATM/ATR and p53 (29). Another possibility for how p53 can be activated in a stress‐dependent manner is p19 ARF induction (or the human equivalent p14 ARF ), which binds to mouse double minute 2 (MDM2 or its human equivalent, human double minute 2, HDM2) and therefore prevents ubiquitination and degradation of p53 (23; Figure 1, Table 1).…”
Section: Somatic Cellular Senescencementioning
confidence: 99%
“…Among the different biological mechanisms that might account for renal aging somatic cellular senescence (SCS) has been proposed as a key contributor (16,(22)(23)(24)(25). SCS describes a phenomenon in which cells are still viable and Telomere attrition or dysfunction can activate p53 and p21 CIP1/WAF1 via the ATM/ATR kinases.…”
Section: Somatic Cellular Senescencementioning
confidence: 99%
See 1 more Smart Citation